Égalité entre les femmes et les hommes et santé au travail - Florence Chappert; Laurence Théry (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article presents the knowledge and research issues that arose from the observation of differences in France in the evolution, by gender, of several occupational health claim indicators. The strong hypothesis developed and tested by the Agence Nationale pour l'Amélioration des Conditions de Travail (National Agency for the Improvement of Working Conditions) is that certain occupational health problems resulting in absenteeism, employee turnover, stress, and occupational wear are dealt with more appropriately when the ergonomic intervention takes into consideration differentiated work situations for men and women based on four factors namely: gender-based work distribution, lack of visible risks or strenuousness, career path, and work time. Despite strong, lingering resistance to “gender,” these elements are now helping to advance regulations and practices in France regarding occupational health and safety and gender equality.